Novel lncRNA-IUR suppresses Bcr-Abl-induced tumorigenesis through regulation of STAT5-CD71 pathway - Wang, Xuefei; Yang, Jianling; Guo, Guijie; Feng, Riyue; Chen, Ke; Liao, Yuan; Zhang, Lianfeng; Sun, Liping; Huang, Shile; Chen, Ji-Long (Molecular cancer, 2019)
Long noncoding RNAs (lncRNAs), defined as the transcripts longer than 200 nt without protein-coding capacity, have been found to be aberrantly expressed in diverse human diseases including cancer. A reciprocal translocation between chromosome 9 and 22 generates the chimeric Bcr-Abl oncogene, which is associated with several hematological malignancies. However, the functional relevance between aberrantly expressed lncRNAs and Bcr-Abl-mediated leukemia remains obscure. LncRNA cDNA microarray was used to identify novel lncRNAs involved in Bcr-Abl-mediated cellular transformation. To study the functional relevance of novel imatinib-upregulated lncRNA (IUR) family in Abl-induced tumorigenesis, Abl-transformed cell survival and xenografted tumor growth in mice was evaluated. Primary bone marrow transformation and in vivo leukemia transplant using lncRNA-IUR knockdown (KD) transgenic mice were further conducted to corroborate the role of lncRNA-IUR in Abl-induced tumorigenesis. Transcriptome RNA-seq, Western blot, RNA pull down and RNA Immunoprecipitation (RIP) were employed to determine the mechanisms by which lncRNA-IUR-5 regulates Bcr-Abl-mediated tumorigenesis. We identified a conserved lncRNA-IUR family as a key negative regulator of Bcr-Abl-induced tumorigenesis. Increased expression of lncRNA-IUR was detected in both human and mouse Abl-transformed cells upon imatinib treatment. In contrast, reduced expression of lncRNA-IUR was observed in the peripheral blood lymphocytes derived from Bcr-Abl-positive acute lymphoblastic leukemia (ALL) patients compared to normal subjects. Knockdown of lncRNA-IUR remarkably promoted Abl-transformed leukemic cell survival and xenografted tumor growth in mice, whereas overexpression of lncRNA-IUR had opposite effects. Also, silencing murine lncRNA-IUR promoted Bcr-Abl-mediated primary bone marrow transformation and Abl-transformed leukemia cell survival in vivo. Besides, knockdown of murine lncRNA-IUR in transgenic mice provided a favorable microenvironment for development of Abl-mediated leukemia. Finally, we demonstrated that lncRNA-IUR-5 suppressed Bcr-Abl-mediated tumorigenesis by negatively regulating STAT5-mediated expression of CD71. The results suggest that lncRNA-IUR may act as a critical tumor suppressor in Bcr-Abl-mediated tumorigenesis by suppressing the STAT5-CD71 pathway. This study provides new insights into functional involvement of lncRNAs in leukemogenesis.